Nanostructured Nonlinear Optical Materials Studies of Clusters, Quantum Dots and Nanoparticles. - Ganeev, Rashid A. (Cambridge Scholars Publishing, 2022)
This highly topical book focuses on novel features and applications of nanostructured nonlinear optical materials. It considers the applications of small-sized multiatomic species for optical limiting, Q-switching, and mode-locking, as well as laser-nanoplasma physics. It will be useful to a wide range of readers, including physicists, material scientists, and engineers interested in material science, plasma physics, laser technology, and spectroscopy.